Pengaruh Karakteristik Individu, Beban Kerja, dan Pengalaman Kerja terhadap Pengembangan Karir Pegawai Puskesmas Simpang Rusa - Taufik Hidayat; Prayekti Prayekti; Kusuma Chandra Kirana (J-MAS (Jurnal Manajemen dan Sains), 2023)
This study aims to examine the effect of individual characteristics, workload, and work experience on the career development of employees at the Simpang Rusa Health Center, Belitung Regency. Integrated into its working area, the Puskesmas is an organizational unit related to health that fosters and provides services to the community as a whole. Puskesmas, like other organizations, need resources to achieve their goals. Human resources are one of the most important resources in the company. The key to the company's success in doing something is these resources. this analysis. using quantitative description method. used multiple linear statistical correlations to examine the relationship between the independent and dependent variables of the study. The results of this study indicate that, although work experience and workload have no effect on employee career development, characteristics have a positive impact on career development, partially and simultaneously. Individual characteristics, workload, and work experience all simultaneously have a positive impact on the career development of Belitung district health center employees. Conclusion: The findings of this study indicate that individual characteristics, workload, and work experience all simultaneously have a positive impact on employee career development.